Tinjauan Pengaruh Omnibus Law Terhadap Penerimaan Negara Dari Perspektif Alkitab - Gilbert Piter Imanuel (Sekolah Tinggi Teologi Jaffray Jakarta, 2020)
This research deals with the effort on how far is the influence of Omnibus Law toward state or federal income in line with taxation and non-taxation. The focus of the research are four folds, namely, First, How does the constitution regulate tax within the context of formal law? ; Second, How does the new regulation set in the Omnibus Law influence the economic and social condition and also the obedience to law within the context of tax law?; Third, How does the Omnibus Law specifically effect the country’s tax based and non tax based revenue? ; Fourth, How can a Christian express their attitude from a Biblical standpoint in relation to the government and taxation specifically tax as the main source of revenue for the country?In providing answers to the questions above, the main topics to be discussed in this research includes 1)The Tax Laws Theory and the Concept of State Revenue, and 2)Implementation of Omnibus Law in relation to the State Tax and Non-tax based Revenue from Biblical View